The factors associated with teenage pregnancy among young women aged between 15 and 19 years in Rwanda: a retrospective cross-sectional study on the Rwanda Demographic Health Survey 2019–2020 - Nduhuye, Felix; Kubana, Emmanuel; Matutina, Stella; Mwesigye, David; Munyaneza, Athanase; Nyirazinyoye, Laetitia (Frontiers in Reproductive Health, 2024)
BackgroundTeenage pregnancy is a significant public health issue and is strongly associated with risky sexual behaviors such as early sexual initiation, unprotected sex, and multiple sexual partners. According to the 2014 World Health Organization report, 11% of all births worldwide were to teenagers aged 15–19 years, with more than 95% of these pregnancies occurring in low- and middle-income countries, particularly in sub-Saharan Africa, which bears much of this burden. In Rwanda, the prevalence of teenage pregnancy has risen from 4.1% in 2005 to 7.3% in 2014, indicating a growing concern. However, there is limited and inconsistent evidence on the factors contributing to teenage pregnancy. Hence, our study aimed to investigate the factors associated with teenage pregnancy. This research seeks to provide valuable insights for targeted interventions, which are urgently needed in light of the increasing rates.MethodsWe employed a cross-sectional study design, utilizing data from the 2019/2020 Rwanda Demographic Health Survey of 3,258 eligible participants aged 15–19 years. To identify factors associated with teenage pregnancy, we performed a bivariate logistic regression analysis. The significant variables from the bivariate analysis were then exported into multivariate logistic regression models, with the results presented as odds ratios (ORs) along with 95% confidence intervals (CIs) and a significance threshold set at 5%.ResultsOur findings indicated that teenagers aged 18–19 years were more likely to experience pregnancy compared to those younger than 17 (OR = 4.2; 95% CI: 2.16–8.37). Adolescents who had engaged in sexual activity 95 times or more had a significantly higher likelihood of becoming pregnant than those with less frequent sexual activity (OR = 13.53; 95% CI: 5.21–35.12). Furthermore, adolescents with parents with a secondary education were 80% less likely to become pregnant compared to those with parents with a primary or no education (OR = 0.2; 95% CI: 0.07–0.63).ConclusionOur study revealed that teenage pregnancy is shaped by several individual factors including age and sexual behavior, along with parental education levels. These findings underscore the critical need for targeted sexual education and enhanced family support systems to mitigate teenage pregnancies. Further, longitudinal studies are essential for establishing causality and guiding effective policy development.